PENGARUH OPINI AUDIT, PROFITABILITAS, SERTA KOMPLEKSITAS OPERASI PERUSAHAAN TERHADAP AUDIT REPORT LAG PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN - Vika Yuliana Putri; Khoirul Abidin (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2022)
This study aims to determine the effect of audit report lag consisting of audit opinion, profitability, and the complexity of the company's operations on food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2020 period. The approach in this study uses quantitative research. The population in this study were 54 manufacturing companies in the food and beverage sub-sector on the Indonesian stock exchange for the 2019-2020 period. The sampling technique used purposive sampling method with the number of companies as many as 27 companies that have a stablecondition. The data collection technique uses research on the financial statements of manufacturing companies in the food and beverage sub-sector on the Indonesian stock exchange for the 2019-2020 period. The data analysis technique used to answer the research hypothesis is multiple linear regression test. The results of this study indicate that the audit opinion variable and the complexity of the company's operations have no effect on the audit report lag, while profitability has an effect on the audit report.